Radial Basis Function Neural Network Model Prediction of Thermo-catalytic Carbon Dioxide Oxidative Coupling of Methane to C2-hydrocarbon - Ayodele B.V. (Springer, 2023)
Calcium oxide; Catalyst selectivity; Cerium compounds; Forecasting; Functions; Greenhouse effect; Greenhouse gases; Hydrocarbons; Manganese oxide; Methane; Network architecture; Oxide minerals; Radial basis function networks; Sensitivity analysis; Anthropogenic activity; Non-linear relationships; Oxidative coupling of methane; Radial basis function artificial neural networks; Radial basis function neural networks; Radial basis functions; Sustainable utilization; Value-added chemicals; Carbon dioxide